Analisis Kandungan Merkuri dan Hidrokuinon dalam Krim Pemutih Wajah Daring Menggunakan Spektrofotometer Serapan Atom dan Kromatografi Cair Kinerja Tinggi - Kusmiyati, Mimin; Tronovani , Elvi; Sulaeman , Agus; Musyarrofah, Laila; Fitriani , Hani Sri; Khotimah , Enung Nur; Mirta, Surya Bin (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
The skin is the outermost organ of the human body and plays an important protective and physiological role. Currently, fair skin is often regarded as a beauty standard desired by both men and women. Mercury and hydroquinone are active ingredients commonly used in whitening products due to their ability to inhibit melanin formation; however, their use can cause serious toxic effects. This study aimed to determine the presence of mercury and hydroquinone qualitatively and quantitatively in facial whitening creams sold online in Bandung City. Samples showing positive results were further analyzed quantitatively to determine their concentrations. For mercury analysis, samples were digested using a microwave digestion method to eliminate organic substances. The color reaction test for mercury employed KI 0.5 N, HCl 6 M, and NaOH 2 N reagents. Based on qualitative testing, samples labeled D and N were positive for mercury. Quantitative determination of mercury was conducted using Atomic Absorption Spectrophotometry (AAS) at a wavelength of 253.7 nm. For hydroquinone analysis, qualitative color tests were carried out using FeCl₃ 5%, phenanthroline, and Benedict reagents, while quantitative analysis was performed using High-Performance Liquid Chromatography (HPLC). Of the 17 samples tested, two (D and N) contained mercury at concentrations of 2,776 ± 0,036 μg/g and 4,277 ± 0,021 μg/g, respectively, and two others (E and H) contained hydroquinone 2,3745% and 2,4798%.